An insight into the remediation of highly contaminated landfill leachate using sea mango based activated bio-char: optimization, isothermal and kinetic studies. Issue 47 (7th October 2016) - Shehzad, Areeb; Bashir, Mohammed J.K.; Sethupathi, Sumathi; Lim, Jun-Wei
Abstract: The feasibility of converting sea mango to activated bio-char that can be used to remove organic and inorganic pollutants such as chemical oxygen demand (COD), color, and ammoniacal nitrogen (NH3 -N) from landfill leachate was investigated in the present study. The preparation conditions, temperature (400–800°C), bio-char impregnation ratio with KOH (0.5–3), and retention time (1–3 h), were optimized using response surface methodology and subsequently analyzed with analysis of variance. Equilibrium data were best dealt with the pseudo-second-order kinetic model, while the adsorptive removal of organic and inorganic pollutants onto sea mango-derived activated bio-char (SMAB) was thoroughly explained by the Langmuir isotherm model. The treatment conditions such as shaking speed, contact time, adsorbent dosage, and pH were also fine-tuned in order to optimize the overall treatment process. The highest adsorptive removal for color (95.1%), COD (84.94), and NH3 -N (95.77) was achieved, respectively. The findings illustrated the applicability of SMAB as an ideal media for the adsorptive treatment of organic and inorganic pollutants from landfill leachate.